Laparoscopic Transcystic Choledochotomy with Primary Suture for Choledocholith - Chen, Dexing (JSLS, 2015)
BACKGROUND AND OBJECTIVES: To investigate the possibility of extracting common bile duct (CBD) stones by laparoscopically inserting choledochoscope through the natural orifice of the cystic duct and a mini-incision on the CBD, and the safety of laparoscopic primary double-layer suture of the cystic duct and CBD. METHODS: Laparoscopic transcystic choledochotomy and extraction of stones with primary suture was performed on 194 patients with gallbladder and CBD stones from October 1, 2009, through April 30, 2012. The cystic duct was left at a diameter of 1 to 1.5 cm after removal of the gallbladder. The duct was longitudinally cut at its ventral side to the confluence with the CBD, and the anterior wall of the CBD was also cut longitudinally. A choledochoscope was then inserted via the enlarged opening, and the stones were extracted from the CBD. Finally, the CBD and cystic duct were closed by continuous mucous layer suture and seromuscular Lembert suture, respectively. The cystic duct was ligated close to the CBD and an abdominal drainage tube was placed. RESULTS: All surgical procedures were successfully performed. The caliber at the confluence between the cystic duct and the CBD was 0.3 to 0.8 cm (SD 0.4 ± 0.1 cm), and the mini-incision of the CBD was 0.1 to 1.1 cm (SD 0.3 ± 0.2 cm). Abdominal drainage lasted 3 to 5 days. Magnetic resonance cholangiopancreatography (MRCP) in 55 patients showed no abnormal change in the CBD diameter. Two patients had bile leakage. Another patient had intermittent abdominal pain and jaundice 5 to 7 days postoperatively, and the retained stones spontaneously passed. The postoperative hospital stay was 6 to 13 days (SD 8 ± 2.1 days). Observation of 176 patients (90%) lasting 1 to 30 months (SD 11 ± 8 months) showed no recurrent stones or stricture of the CBD. CONCLUSION: The surgical procedure of laparoscopic transcystic choledochotomy and extraction of stones with primary suture is feasible and safe.